ASSESSING THE RISK OF LOSS OF WORLD CULTURAL HERITAGE IN THE EVENT OF A FULL-SCALE INVASION BY RUSSIA INTO UKRAINIAN TERRITORY - KOVALOVA, Viktoriia; KHOROLSKY, Valentyn (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study actualizes the problem of preserving cultural property in the period of unusual situations and Russia’s war against Ukraine. A mechanism for their preservation during the war was developed by establishing adequate communication between cultural organizations and authorities at all levels, regional military administrations, using international mechanisms for the protection of cultural heritage. Making decisions regarding the preservation of cultural values in the conditions of uncertainty. Therefore, it requires a systematic approach to identifying possible unusual, abnormal situation and events.Their timely recognition and prediction to the decision maker (DM) allows for real-time counteraction to unusual events. The architecture of a general algorithm for the functioning of the risk management system of a cultural organization in the context of man-made and of dangerous events. The architecture of a general algorithm for the functioning of the management system of risks of cultural organization in the territory with man-made events and military operations. It operates in the mode of information and decision-making support for risk management by cultural organizations. This intelligent system allows to create a single expert assessment of situations (ESS) with the Ministry of Culture and the Minister of Information Policy of Ukraine to build a multifunctional management system for protecting the territory from enemy missile attacks. The proposed intelligent system, with the help of the ISPSR and ISPKR, recommends DM expert assessments: the impact of abnormal situations on the biota of the territory, integrated climate change indicators, CO2 deviations from EU standards, water level factors and methods of protecting dams from missile attacks and integrated risk management solutions. The developed approach allows the DM to optimize decision-making in the face of uncertainty and communicate with other institutions to protect cultural sites in times of war and other man-made threats.
Keywords: cultural objects; events; risks; situation monitoring; interaction of cultural organizations; decision-making systems; uncertainty